Grundtvig i angelsaksisk kontekst - Balslev-Clausen, Peter (Grundtvig-studier, 1994)
Grundtvig in Anglo-Saxon context.Heritage and Prophecy. Grundtvig and the English-Speaking World. Edited by A.M. Allchin, D. Jasper; J.H. Schj.rring and K. Stevenson. Aarhus University Press, .rhus 1993. 330 s. ISBN 87 7288 447 9. Skrifter udgivet af Grundtvig-Selskabet, bind XXIV.Reviewed by Peter Balslev-Clausen